Paesaggio e Storia - Nanni, Paolo (Ri-Vista. Research for landscape architecture, 2015)
The history of agrarian landscape combines different research perspectives. In this mosaic, historical study has its own peculiarities connected with the specific object of history (formal object) and therefore with investigation methodologies. By references to historiographic examples, this article illustrates the research perspective through which historical study investigates the agrarian landscape. Finally, the article describes some effects on the current context: the knowledge and understanding of agrarian landscape, and its past and present connections with agriculture, allows to tackle more properly some tricky issues such as, e.g., the extension of the notion of landscape protection to agrarian landscape.